Out-patient surgical prophylaxis Prospective study (Mustansiria Dental Journal, 2018)
Antibiotic prophylaxis in oral surgery is well established practice; still there is no specific protocol followed in Iraqi dental surgical centers. The aim of this study is to compare between efficiency of 3 prophylactic protocols in preventing post operative infection and reducing healing period in out patient’s oral surgical procedures. Forty four patients, selected from the attendants of oral surgery clinic in college of dentistry Almustansiriyah University, were subjected to different oral surgical procedures (45 operations) under local anesthesia. These patients were given single dose antibiotic prophylaxis in 3 groups; 1st group were given 1 million i.u. of procaine penicillin (15 cases), 2nd group were given 500 mg ampicilline vial (15 cases), 3rd group were given 1 gm amoxicillin (15 cases). The maximum time for all procedures was 2 hours. We conclude that there is no difference between ampicilline (500mg), procaine penicillin (1 million i.u.), and Amoxicillin (1 gm) regimens concerning post operative infection, while patients of the 1st group healed in a shorter period than other two groups.